Rationale and design of the theRapeutic effects of peroneal nerve functionAl electrical stimuLation for Lower extremitY in patients with convalescent poststroke hemiplegia (RALLY) study: study protocol for a randomised controlled study - Shuji Matsumoto; Megumi Shimodozono; Tomokazu Noma (BMJ Open)
Introduction Increasing evidence supports the utilisation of functional electrical stimulation (FES) to improve gait following stroke; however, few studies have focused exclusively on its use in the convalescent phase. In addition, its efficacy in patients with a non-Western life style has not been evaluated.Methods and analysis This is a randomised, controlled, open-label multicentre study, comparing rehabilitation with and without FES. The purpose of our study is to test the hypothesis that the FES system improves walking ability in Japanese patients with hemiplegia during the convalescent phase. Two hundred patients aged 20–85 years who had an initial stroke ≤6 months prior to the enrolment, are in a convalescent phase (after the end of acute phase treatment, within 6 months after the onset of stroke) with functional ambulation classification 3 or 4 and have a hemiplegic gait disorder (drop foot) due to stroke have been recruited from 21 institutions in Japan. The patients are randomised in 1:1 fashion to usual gait rehabilitation or rehabilitation using FES (Walkaide). The trial duration is 8 weeks, and the primary outcome measured will be the change in maximum distance from baseline to the end of the trial, as measured with the 6 min walk test (6-MWT). The 6-MWT is performed barefoot, and the two treatment groups are compared using the analysis of covariance.Ethics and dissemination This study is conducted in accordance with the principles of the Declaration of Helsinki and the Ethical Guidelines for Medical and Health Research Involving Human Subjects and is approved by the ethics committee of all participating institutions. The published results will be disseminated to all the participants by the study physicians.Trial registration number The University Hospital Medical Information Network-Clinical Studies Registry (UMIN000020604).